(untitled) (Journal of Human Sciences, 2026)
This study explores the reasons why Libyan students decide to pursue postgraduate studies. In this study, the factors that motivate them to pursue their studies both at university and The Libyan Academy are investigated to create a broader understanding of their purposes in enhancing their academic career and social status as well. The sample consists of 82 students (female = 70 (85.4%) and male = 12 (14.6%)) who are master/PhD degree students studying in different fields at the Libyan Academy and university. The data are obtained from a close-ended questionnaire in a Likert type scale with adequate validity and reliability and a semi-structured interview. The qualitative data obtained from the semi-structured interviews were analyzed thematically and the quantitative data were analyzed employing percentages. The results reveal that there are no differences in motivating factors for having degrees between male and female students. However, the motives for pursuing postgraduate studies vary displaying ambition and reality of doing these studies. The results also show the reality of doing postgraduate studies locally and the associated barriers.